2016
DOI: 10.18699/vj15.116
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of cyclophosphamide, dsDNA preparations and combinations thereof against Krebs-2 ascites cancer cells and various cancer transplants

Abstract: Федеральное государственное бюджетное научное учреждение «Федеральный исследовательский центр Институт цитологии и генетики Сибирского отделения Российской академии наук», Новосибирск, Россия 2 Федеральное государственное автономное образовательное учреждение высшего образования «Новосибирский национальный исследовательский государственный университет», Новосибирск, Россия 3 Федеральное бюджетное учреждение науки Государственный научный центр вирусологии и биотехнологии «Вектор», р. п. Кольцово,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Earlier, we performed comprehensive analysis of cellular and molecular events accompanying the therapy [ 6 , unpublished data] and conclude that the effects observed are based on the selective targeting of Krebs-2 TISCs, which neutralizes the tumorigenic potential of cancer cells [ 2 ]. So, we suggested that multiple injections in the metronomic regimen could be substituted by a single injection of a composite dsDNA preparation at the 18 h timepoint post CP (6 mg total) to fully recapitulate the desired therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we performed comprehensive analysis of cellular and molecular events accompanying the therapy [ 6 , unpublished data] and conclude that the effects observed are based on the selective targeting of Krebs-2 TISCs, which neutralizes the tumorigenic potential of cancer cells [ 2 ]. So, we suggested that multiple injections in the metronomic regimen could be substituted by a single injection of a composite dsDNA preparation at the 18 h timepoint post CP (6 mg total) to fully recapitulate the desired therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…An increased percentage of this type of cells over the background of a drastic decrease in the number of committed tumor cells (the bulk of tumor cells) testified for exactly the such events flow. This finding denoted the most important time point in the therapy, when all remaining tumor cells, both committed and stem-like, are synchronized in G2/M phases [29][30][31][32][33].…”
Section: Brief History and Main Stages Of The "Karanahan" Developmentmentioning
confidence: 72%
“…6, 3) схематично изображена динамика накопления, репарации и исчезновения двуцепочечных разрывов, вызванных действием цитостатика ЦФ. Сплошными линиями изображены ранее полученные экспериментальные данные, пунктиром -предположительный путь развития репаративных событий на основании уже имеющихся данных (Поттер и др., 2016;Dolgova et al, 2014).…”
Section: характеристика токсического синергичного действия циклофосфаunclassified